To Compare the Outcomes of Laparoscopic and Open Appendectomies (Medical Forum Monthly, 2024)
Objective: To compare the surgical site infection, hospital stay and time duration of procedure in patients undergoing laparoscopic and open appendectomies. Study Design: Prospective study. Place and Duration of Study: The study was conducted at the Department of Surgery, Bolan University of Medical & Health Sciences, Quetta from January 2017 to February 2019. Materials and Methods: Two hundred male/female patients with ages >10 years presented with acute appendicitis were included. Patients demographic including age, sex and body mass index were recorded after written consent. Equally divided all the patients into two groups. Group-I (Laparoscopic appendectomy) consist of 100 patients and Group II (Open appendectomy) with 100 patients. Outcomes such as surgical site infection, hospital stay and time duration of procedure were examined and compare the results between both groups. SPSS 24.0 was used fr analyzing the data. Results: here were 110 (55%) patients (52 Group I, 58 Group II) were male with mean age 24.3+7.45 years while 90 (45%) patients (48 Group I, 42 Group II) were females with mean age 25.2+8.2 years. No significant difference regarding BMI between both groups p=>0.05. Significant difference was observed in term of surgery time duration between both groups 45.42+10.95 minutes Vs 30.48+9.68 minutes (P=0.001). No significant difference observed in term of hospital stay (p=0.345). 10 (10%) patients in GroupII and 6 (6%) patients in Group I had developed surgical site infection with no significant difference (p=0.41). Conclusion: Open appendectomy is better in term of operative time as compared to laparoscopic appendectomy. We found no significant difference regarding surgical site infection and hospital stay.